Comparing child protection decision-making in England and Finland: supervised or supported judgement?. Issue 2 (3rd April 2018) - Falconer, Rachel; Shardlow, Steven M.
ABSTRACT: Systems for the protection of children have evolved differently across nation states. Studies have identified contrasting system 'orientations', related to how child protection problems are framed and how organisations respond in different contexts. In this study, the influence of national and organisational factors on practice-level decision reasoning by social workers has been compared. Interviews were conducted with 30 child protection social workers in sites across England and Finland, structured around two hypothetical case vignettes. While similarities were observed in how the social workers responded to the vignettes, there were differences in the nature and extent of managerial involvement described, with the English social workers appearing to rely on managerial input for decision-making to a greater extent than the Finnish social workers. These findings suggest evidence for two distinct organisational approaches to decision-making: 'supervised' and 'supported' judgement. Here, supervised judgement describes a hierarchical, 'top-down' form of decision-making, while supported judgement describes a more horizontal and shared decision-making approach. The lens of comparative methodology has revealed how these organisational factors come into play in different child protection systems. The practice implications of supervised, manager-led approaches to decision-making, as contrasted with supported, team-led approaches, are discussed.